The ‘Ivory Tower’ exposed: The university in Ashour’s Atyaf and Coetzee’s Disgrace - Massoud, Fatma Atef Ibrahim (AUC Knowledge Fountain, 2016)
The sub-genre of the campus novel is relatively new, only starting in its recent form in the mid-fifties in England and the United States. There have been attempts for writing campus novels in Arabic modern fiction, but none of them were consciously categorized under this sub-genre; the term is fairly new to the Arabic literary scene. This thesis is a comparative study of Atyaf (Specters) (1999), an Egyptian modern campus novel by writer and professor Radwa Ashour (1946-2014), which ushers this sub-genre in Arabic literature, and Disgrace, by South African writer and Professor J. M. Coetzee (1940- ). Atyaf is semi-autobiographical, with an intersection of the life of a fictional character into the narrator’s own. Creating a double corresponding to the main character is indicative, of double trajectories that could have been undertaken. Disgrace, though fictional, overlaps with Coetzee’s professional career as a professor at Cape Town University. As an academic, Ashour firmly believed in institutional autonomy and academic freedom and struggled against authoritarian surveillance in the university. Coetzee wrote intensively on the importance of establishing institutional autonomy and defending academic freedom. He also had expressed concerns about intellectuals and their role inside the walls of the university. By exposing corruption, revealing issues of lack of intellectual integrity, hypocrisy, abuse, academic life in the so-called ‘Ivory-Tower,’ I attempt to explore how both Ashour and Coetzee expose the reality of the university against its idealistic, utopian picture as woven in the consciousness of the public. The thesis addresses the image, role, function, and social position of the intellectual and the University as presented in theoretical works of Edward Said, touching on definitions by Martin Heidegger, Cardinal Newman, Michel Foucault, Paul Baran, and Taha Hussein.